Improving Science Learning Outcomes through Student Team Achievement Division (STAD) - Dewi, Luh Monik Septiani; Wibawa, I Made Citra; Tri Agustiana, I Gusti Ayu (Universitas Pendidikan Ganesha, 2020)
The low student learning outcomes of Science competencies are experienced by many students. The causes of the decline in science learning outcomes are the teacher's love for one learning method and the use of inadequate learning models so that students find it difficult to understand learning, lack of communication and participation between students which causes students to be less courageous in asking and arguing so learning is not optimal, students still lacking discipline during learning takes place. Based on the description, the purpose of this study is to determine the significant effect of the STAD Cooperative Model on Science Learning Outcomes. This study uses the design of a non-equivalent post-test only control group design with an intact group random sampling technique. The total population of this study was 95 students and the total sample in this study amounted to 49 students. The method used is a test with multiple-choice instruments totaling 20 items. The data obtained were analyzed using descriptive statistical analysis and inferential analysis with data distribution normality test, variant homogeneity test (F-Test), and hypothesis testing (t-test) using the pooled variance formula. The results of data analysis using the t-test obtained by t-count 2.540 while the table with db = 47 of 2.067 with a significance level of 5%. The results showed that there was a significant influence on the learning outcomes of science groups of students who were taught with the STAD type cooperative model with groups of students who were not taught with the STAD type cooperative model. The STAD type cooperative model makes students the center of learning through the application of the STAD type cooperative model students are motivated to compete in understanding lessons, train women in expressing opinions, discipline and take responsibility for themselves and the group.